Laboratory evaluation on performance of porous polyurethane mixtures and OGFC. (30th April 2018) - Cong, Lin; Wang, Tongjing; Tan, Le; Yuan, Junjie; Shi, Jiachen
Highlights: The laboratory test results show that PPM2 has the potential to substitute traditional OGFC. The fatigue life of PU-bonded porous mixtures was over one order of magnitude greater than that of asphalt porous mixtures. Generally, the mechanism of PU is between that of asphalt and cement. By increasing Tg of PU binder, the severe moisture damage problems in PPM were solved. Abstract: The application of open grade friction course (OGFC) is limited by problems such as mixture disintegration and relatively poor fatigue performance. In this study, polyurethane (PU), a polymer binder, and PU-bonded mixtures were studied for overcoming the limitations of traditional asphalt-bond OGFC mixtures. The viscosity-time and mechanical properties of two PU binders were characterized using Rheometer, tensile test and dynamic mechanical analysis (DMA). Then a laboratory evaluation of the PU-bonded porous mixtures (PPM) and asphalt-bonded porous mixtures (APM) were undertaken using the Marshall stability test, the Cantabro Loss test, and the fatigue test. The test results show the PPM obtained three times higher stability and over one order of magnitude greater fatigue life than APM. When compared with the low glass-transition temperature ( T g ) PU binder, the high T g PU binder significantly improved resistance to moisture damage and lowered Cantabro loss of PPM in the 60 °C immersion conditions. Results of this study will provide an important reference for utilizing PU porous mixtures as OGFC surface layer, and discover ways to improve OGFC durability.